2006
DOI: 10.1063/1.2176238
|View full text |Cite
|
Sign up to set email alerts
|

An integrated microfluidic cell for detection, manipulation, and sorting of single micron-sized magnetic beads

Abstract: A lab-on-a-chip integrated microfluidic cell has been developed for magnetic biosensing, which is comprised of anisotropic magnetoresistance (AMR) sensors optimized for the detection of single magnetic beads and electrodes to manipulate and sort the beads, integrated into a microfluidic channel. The device is designed to read out the real-time signal from 9μm diameter magnetic beads moving over AMR sensors patterned into 18×4.5μm rectangles and 10μm diameter rings and arranged in Wheatstone bridges. The beads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 18 publications
0
37
0
Order By: Relevance
“…In this respect, magnetoresistive sensors, especially those relying on the GMR effect represent an efficient solution for the use in fluidic biodetection platforms due to their high sensitivity 195 . Planar 88,196,197 as well as rolled-up 85 magnetic sensors are already incorporated in microfluidic channels enabling detection of magnetic particles. The fabrication of these magnetic sensors requires intensive lithography processing and is therefore expensive and time consuming 187,190 .…”
Section: Gmr Sensors In Circumferential Geometrymentioning
confidence: 99%
“…In this respect, magnetoresistive sensors, especially those relying on the GMR effect represent an efficient solution for the use in fluidic biodetection platforms due to their high sensitivity 195 . Planar 88,196,197 as well as rolled-up 85 magnetic sensors are already incorporated in microfluidic channels enabling detection of magnetic particles. The fabrication of these magnetic sensors requires intensive lithography processing and is therefore expensive and time consuming 187,190 .…”
Section: Gmr Sensors In Circumferential Geometrymentioning
confidence: 99%
“…19 While useful, these investigations do not provide a quantitative particle-tracking model that is applicable regardless of configuration and geometry. Previous simulations of magnetic particle transport in microfluidic contexts 20 have also not focused on individual particle trajectories or detailed parametric analyses.…”
mentioning
confidence: 99%
“…The susceptibility of paramagnetic materials can be very small compared to ferromagnetic materials. 35 It was shown that magnetic moment of individual ferromagnetic bead is approximately ten times more than the same size superparamagnetic bead; 36,37 this fact resulted in longer bead chains and faster response to magnetic field in our experiments.…”
mentioning
confidence: 71%
“…The excessive dye was rinsed off with water to complete the standard simple staining procedure. 37,39 To perform magnetic dipole-dipole interaction, ferromagnetic beads (8 μm) suspended in PBS buffer added to stained bacteria and the platform, including permanent magnets, were placed on the two sides of the droplet on the glass slide, as in Figure 7. The anti-E. coli magnetic beads were attracted to ferromagnetic beads as a result of magnetic dipole-dipole interaction forming an accumulation as:…”
Section: Magnetic Accumulation On E Coli Samplesmentioning
confidence: 99%